2016
DOI: 10.1016/j.mechmat.2015.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale structure modeling of damage behaviors of 3D orthogonal woven composite materials subject to quasi-static and high strain rate compressions

Abstract: We proposed a multi-scale structure modeling scheme to analyze the damage behaviors of three-dimensional orthogonal woven composite materials subject to quasi-static and high strain rate compressions. The multi-scale structure model includes: (1) micro/meso/macro structure model with periodic boundary conditions for homogenizing the heterogeneous fiber/resin system into unit cells, and (2) a macroscopic rate dependent plasticity model combined with critical damage area failure theory that accounts for the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 99 publications
(95 reference statements)
0
21
0
Order By: Relevance
“…Fiber-reinforced polymer (FRP) composites are increasingly used in impact-resistant devices, automotives, biomedical applications and aircraft structures due to their high strength-to-weight ratios and their potential for impact energy absorption [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. FRP composites are often treated as softening materials, i.e., materials that show a reduction of the load-carrying capacity accompanied by increasing (localized) deformations after reaching the maximum load-carrying capacity [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fiber-reinforced polymer (FRP) composites are increasingly used in impact-resistant devices, automotives, biomedical applications and aircraft structures due to their high strength-to-weight ratios and their potential for impact energy absorption [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ]. FRP composites are often treated as softening materials, i.e., materials that show a reduction of the load-carrying capacity accompanied by increasing (localized) deformations after reaching the maximum load-carrying capacity [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the FE results revealed that the braiding structure had a significant influence on thermomechanical failure. A multi-scale approach and the CDA theory were also employed in the study of high-strain-rate compression (Wan et al 2016).…”
Section: High-velocity and Ballistic Impactmentioning
confidence: 99%
“…18 Three dimensional (3 D) woven fabrics provide better reinforcement through the thickness direction of composite structures than 2 D fabrics due to their high inter-laminar strength and structural integrity, and more recently, the investigation of 3 D fabrics as reinforcement for composites draws increasing attention in the composites community. 1921 3 D woven fabrics are integrated woven spacer composites typically consist of two discrete fabric layers and an integrated hollow core. 22 Wang et al.…”
Section: Introductionmentioning
confidence: 99%